Effectiveness Test of Saliara Leaf Extract (Lantana camara) on Escherichia coli Bacteria Kirby Bauer Disc Method - Baba, Firda; Karim, Marzelina; Sam, Andi Dhedie Prasatia; Sodiqah, Yani; Hatta, Dhian Karina (Jurnal Biologi Tropis, 2024)
Death due to infection is the most common cause and is a challenge in the health sector. In 2019, 7.7 deaths were due to bacterial infections, 90 to 100 cases were urinary tract infections and Escherichia coli bacteria contributed to 90% of urinary tract infections. This research uses the Kirby Bauer Disc method to determine the effectiveness of Saliara (Lantana camara) leaves against Escherichia coli bacteria. The type of research is a Laboratory experiment using the Kirby Bauer disc method with a post-test-only control group design. Data analysis uses recording of identifying the inhibition zones formed The research showed that a sample’s concentration can influence the inhibition zone’s resulting diameter. Saliara leaf extract with concentrations of 100%, 150%, and 200% produced an inhibition zone of 8.55 mm; 9.59mm; 12.34 mm in the proliferation of Escherichia coli bacteria. The positive control with the antibiotic ciprofloxacin produced an inhibition zone of 19.56 mm on the growth of Escherichia coli bacteria. Control with negative distilled water does not create an inhibition zone because it does not have antibacterial activity. The conclusion is moderate inhibitory activity in Saliara (Lantana camara L.) leaf extract at concentrations of 100% and 150%. It is strong at a concentration of 200% against the growth of Escherichia coli bacteria.